Expression of matrix metalloproteinases (mmp-2) in prognostication of meningioma - Sharifuddin, Maryam Ahmad (2020)
Background: Meningioma is the most common intracranial tumour in adults which is 20% of all primary intracranial tumours. Besides extent of tumour surgical resection and WHO grading, angiogenesis is also one of the prognostic factors, which is influenced by MMP-2. Our study aimed to determine the association of these prognostic factors with expression of MMP-2 in meningioma. Methodology: A cross sectional study was conducted on 99 samples of meningioma of different grades diagnosed from January 2008 until December 2017. All samples were re-reviewed and stained with Ki67, MMP-2 and CD34 immunohistochemistry markers. Pearson chi square and Fischer’s exact test were used to examine the association between MMP-2 expression with WHO grades and Microvascular Density (MVD). Results: A total of 99 cases consists of patients aged between 23 to 75 years old. Majority of patients were female (73.7%). This study consists of 85 cases of low-grade meningioma (Grade I) and 14 cases of high-grade meningioma (11 = Grade II, 3 = Grade III). The most common subtypes are meningothelial, transitional and fibroblastic. Sixty two out of 85 cases of low-grade and 10 out of 14 cases of high-grade shows high MMP- 2 expression, however they were not significant, p >0.950. Most of the cases in this study exhibits low level of angiogenesis with MVD score of 1+ (54/99) and 2+ (33/99). Out of the 54 cases that scored 1+, 42 expressed high MMP-2. However, this is not significant. Conclusion: MMP-2 were expressed in all low- and high-grade meningiomas with varying intensity. Majority of cases exhibit low quantity of angiogenesis and among these cases, mostly expressed high MMP-2. However, these findings were not significant. In future study, more higher grade meningioma is required to prevent bias in analyzing data. A more specific immunohistochemical marker should be used to evaluate angiogenesis to achieve accurate scoring.